Manajemen Hakim (Studi Perbandingan Indonesia dengan Turki) - Azhar, Ikhsan (Jurnal Mulawarman Law Review, 2018)
In the past three years, the profession as a judge has been in the spotlight. The reason is because this profession can be referred to as "God’s Deputy" and as a place for the last hope of the public in seeking justice it turns out that it was also been exposed by the Corruption Eradication Commission’s sting operation (KPK OTT) and so many were proven and punished for violating ethics. This is the reason why the urgency of the management of judges will be echoed. To make improvements, the research should not stand alone, but also see the practice of independence from the judicial power institutions and similar institutions of Judicial Commission (KY). In this regard, it is important to study with practice abroad, which in this paper takes Turkey as the comparative country of Indonesia. It is hoped to get a picture of practices from other countries, there are lessons that can be adopted in Indonesia to be regulated and practiced. In order for writing to be more focused the author uses normative legal research methods with a comparative approach. After studying the material and data, there are several results of this study, including the first judicial power institutions in Turkey and Indonesia which are independent institutions, and are equally regulated in the constitution, especially the judicial power chapter; second, the history of reform in implementing the management functions of judges in Turkey and Indonesia is different. If in Turkey it is done by separating it from the executive institution by establishing an HCJP institution, while in Indonesia it is carried out by being united to the judicial power institution; third, in Turkey the management of judges such as recruitment, regulating the placement, promotion, transfer, supervision, and imposition of disciplinary measures is carried out by other institutions called HCJP, while in Indonesia the management of judges is carried out by the Supreme Court. Even though KY has a duty in relation to the management of the judge's position, only in terms of training and supervision; fourth, HCJP and KY are equally regulated in the constitution, especially the judicial power chapter, and also have their own technical rules made to facilitate the implementation of their authority and duties.